2016
DOI: 10.17512/ios.2016.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salinity and Water Level of the Lake Jamno Resulting from the Construction of Storm Gates

Abstract: Zmiany zasolenia i poziomu wody jeziora Jamno wynikające z budowy wrót przeciwsztormowych Changes in Salinity and Water Level of the Lake Jamno Resulting from the Construction of Storm GatesThe aim of the study is to determine changes in salinity and water level of the Lake Jamno, which occurred as a result of the construction of the storm gate. It is very important aspect, as in the case of coastal lakes rather seeks to "open" object on the direct impact of the sea, and not his "closing". Of course there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was found that in the years 1889-2006, the maximum water levels increased on average from 0.39 cm/year inŚwinoujście and Kołobrzeg to 0.54 cm/year in Gdańsk [6]. It is worth noting that correlations between the studied coastal lakes and the Baltic Sea refer not only to their water levels: the coast of the Baltic Sea is a place where high qualitative and quantitative variability of biotic [16][17][18][19][20] and abiotic elements [7][8][9][10][11][12][13]23] is observed, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that in the years 1889-2006, the maximum water levels increased on average from 0.39 cm/year inŚwinoujście and Kołobrzeg to 0.54 cm/year in Gdańsk [6]. It is worth noting that correlations between the studied coastal lakes and the Baltic Sea refer not only to their water levels: the coast of the Baltic Sea is a place where high qualitative and quantitative variability of biotic [16][17][18][19][20] and abiotic elements [7][8][9][10][11][12][13]23] is observed, too.…”
Section: Discussionmentioning
confidence: 99%
“…The relation strength between maximum water levels of the sea and coastal lakes may increase in the future due to sea level rises caused by climate warming.Coastal lakes are characterized by complex water circulation related to their location at the interface of two "environments", sea and land, and they supply marine waters and river waters from inland areas. Research on coastal lakes in Poland and in the world has covered issues concerning, among other things, the chemistry/quality of water (including its salinity) [7][8][9][10][11][12][13], the development of lakes in the Holocene [14], the trophic status of lakes in the Holocene [15], biodiversity [16][17][18][19][20], sea water intrusions [4,21,22], and ice phenomena [23]. All of these said studies have confirmed the effect of the sea on the aforementioned properties of lakes.Water level fluctuations in lakes have various characteristics and causes.…”
mentioning
confidence: 99%